Pomen nove oblike pisnega navodila za bolnike z antikoagulacijskim zdravljenjem - Kramarič, Anja (Zdravniški vestnik, 2009)
Background Monitoring of warfarin therapy is difficult, as it is often followed by complications as haemorrhage or thrombembolic events. To assure safe and sufficient anticoagulation, adequate patient knowledge is needed. Beside short educational course before starting the treatment, written information is of crucial value. Aims To examine if new launched booklet for patients improves comprehension and knowledge about anticoagulant treatment. Patients 286 patients, aged 67 ( 13) years, were included. The questionnaire was administrated to a group of 235 patients and re-administrated 2 months after receiving the new booklet. Control group of 51 patients was examined only after new booklet was administrated. Results The new booklet was read by 90.1 % patients. There was no significant difference in the knowledge of stepsin case of a major bleeding before and after administration of the new booklet. There was a significant increase in knowledge of the indication for anticoagulant treatment (p = 0.01), importance of regular monitoring (p = 0.001), awareness of the risks associated with anticoagulation treatment (p = 0.001), steps in case of minor bleeding (p = 0.0005) and invasive procedures (p = 0.0005), consuming fruit and vegetables (p = 0.0005), in taking drugs that may interfere with warfarin (p = 0.0005). After administration of the neweducational booklet the number of collected total points was significantly higher (14 3 vs. 17 3 points; p = 0.0001). Score achieved after the administration of the booklet was not significantly different from that achieved in the control group. Conclusions Knowledge about anticoagulation therapy was significantly improved after the administration of the new booklet. For the small group of patients whose knowledge did not improve, new forms of education are needed.
Keywords: ankete; Anticoagulants; antikoagulacijsko zdravljenje; Antikoagulansi; Bolnik, izobraževanje; krvavitve; navodila; Patient Education; Questionnaires; Therapeutic Use; Varfarin; Warfarin